The Spatiotemporal Control of Zygotic Genome Activation - Gentsch, George E.; Owens, Nick D.L.; Smith, James C. (iScience, 2019)
One of the earliest and most significant events in embryonic development is zygotic genome activation (ZGA). In several species, bulk transcription begins at the midblastula transition (MBT) when, after a certain number of cleavages, the embryo attains a particular nuclear-to-cytoplasmic (N/C) ratio, maternal repressors become sufficiently diluted, and the cell cycle slows down. Here we resolve the frog ZGA in time and space by profiling RNA polymerase II (RNAPII) engagement and its transcriptional readout. We detect a gradual increase in both the quantity and the length of RNAPII elongation before the MBT, revealing that >1,000 zygotic genes disregard the N/C timer for their activation and that the sizes of newly transcribed genes are not necessarily constrained by cell cycle duration. We also find that Wnt, Nodal, and BMP signaling together generate most of the spatiotemporal dynamics of regional ZGA, directing the formation of orthogonal body axes and proportionate germ layers.